Radiological and serological predictors of cavitary transformation in rheumatoid arthritis-associated pulmonary nodules: a retrospective cohort study - Oz, Burak; Dogan, Yusuf; Karatas, Ahmet; Koca, Suleyman Serdar (Springer London Ltd, 2025)
Background/ObjectivesCavitary pulmonary nodules (CPN) represent a rare but clinically relevant manifestation of rheumatoid arthritis (RA), yet their radiological and serological predictors remain poorly defined. This study aimed to identify key clinical, immunological, and imaging features associated with CPN among RA patients presenting with pulmonary nodules (PN).MethodsThis retrospective cohort included 156 RA patients with PN identified on thoracic computed tomography between 2010 and 2024. Clinical data, autoantibody status, treatment characteristics, and radiological parameters were compared between patients with and without CPN.ResultsCPN were detected in 9.0% (n = 14) of cases. Compared to patients without CPN, affected individuals had a significantly greater number of nodules, larger nodule diameters, and higher seropositivity for rheumatoid factor, anti-cyclic citrullinated peptide antibodies, and ANCA. The largest nodule diameter was the only independent predictor of cavitary transformation (OR: 1.59, 95% CI: 1.19-2.12; p = 0.002), with stronger effect sizes in penalized regression (OR: 6.69 per SD; 95% CI: 3.52-12.61). Despite limited sample size, ROC analysis identified an optimal cut-off of 18 mm, yielding excellent discriminative performance (AUC: 0.979; sensitivity: 92.9%, specificity: 95.8%), further supported by bootstrap validation. No significant differences in baseline treatments were observed, though greater variability in drug exposure and post-diagnostic therapy adjustments was noted in CPN-positive patients.ConclusionsRadiological morphology-particularly increased nodule size-alongside autoantibody positivity, are key correlates of cavitary transformation in RA-associated PN. These findings support the use of imaging-based risk stratification and highlight the need for prospective validation across broader RA populations. Key Points center dot CPN were detected in 9% of RA patients with PN on CT imaging center dot Larger PN diameter emerged as the principal independent predictor of cavitary transformation, with an18 mm cut-off providing high discriminative capacity (AUC = 0.979).center dot Seropositivity for RF, anti-CCP, and ANCA IFA was significantly associated with cavitation.center dot Greater heterogeneity in pre-diagnostic leflunomide exposure and more frequent post-diagnostictherapy modifications among CPN-positive patients suggest a dynamic and potentially treatmentinfluenceddisease pattern, possibly reflecting variability in therapeutic response over time.
Keywords: Cavitary lesions; Pulmonary nodules; Rheumatoid arthritis